Benin - Improving Budget Systems To Increase Poverty Alleviation Impact - World Bank (Washington, DC, 2012)
The Public Expenditure Review (PER) in Benin is considered an integral component of the structural adjustment program. The process is multi-year and multi-sectoral, in order to allow the government to thoroughly analyze every sector's expenditures for consistency with its corresponding sector strategy and the general macroeconomic framework. Four main issues were addressed: a) the role of the state vis-a-vis the private sector; b) the efficiency of expenditures as measured by results achieved and their coherence with the sector strategy targets; c) the equity of expenditures measured by their contribution to promote more equal distribution of revenues and welfare; and d) budgetary procedures and institutional arrangements.